2011
DOI: 10.1007/s00266-011-9851-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Continuous Elastic Outside Distraction on the Expressions of Vascular Endothelial Cell Growth Factor and Microvessel Density in Female Porcine Nipple

Abstract: Continuous elastic distraction can promote the expression of some growth factors in nipples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Traction and expander techniques can promote tissue regeneration, and the longer the treatment duration, the more tissue will be obtained, thus over correction can prevent recurrence. In an animal study, Zhou et al 14 reported that continuous elastic distraction can increase tissue development by promoting the expression of vascular endothelial cell growth factor and the microvessel density in nipples. Traction can also elongate the contraction fibrous tissue and lactiferous ducts, and without the scar contracture accompanied by traditional surgical technique, thus the recurrence is lower.…”
Section: Discussionmentioning
confidence: 98%
“…Traction and expander techniques can promote tissue regeneration, and the longer the treatment duration, the more tissue will be obtained, thus over correction can prevent recurrence. In an animal study, Zhou et al 14 reported that continuous elastic distraction can increase tissue development by promoting the expression of vascular endothelial cell growth factor and the microvessel density in nipples. Traction can also elongate the contraction fibrous tissue and lactiferous ducts, and without the scar contracture accompanied by traditional surgical technique, thus the recurrence is lower.…”
Section: Discussionmentioning
confidence: 98%